If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(7x + 6) = 7(8x + -3) Reorder the terms: 6(6 + 7x) = 7(8x + -3) (6 * 6 + 7x * 6) = 7(8x + -3) (36 + 42x) = 7(8x + -3) Reorder the terms: 36 + 42x = 7(-3 + 8x) 36 + 42x = (-3 * 7 + 8x * 7) 36 + 42x = (-21 + 56x) Solving 36 + 42x = -21 + 56x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-56x' to each side of the equation. 36 + 42x + -56x = -21 + 56x + -56x Combine like terms: 42x + -56x = -14x 36 + -14x = -21 + 56x + -56x Combine like terms: 56x + -56x = 0 36 + -14x = -21 + 0 36 + -14x = -21 Add '-36' to each side of the equation. 36 + -36 + -14x = -21 + -36 Combine like terms: 36 + -36 = 0 0 + -14x = -21 + -36 -14x = -21 + -36 Combine like terms: -21 + -36 = -57 -14x = -57 Divide each side by '-14'. x = 4.071428571 Simplifying x = 4.071428571
| 15=-6w+3(w-2) | | -0.10(89)+0.85x=0.05(x-18) | | 9w-5w=12 | | 11z-6(2z+5)= | | 74x-3=4 | | 2/3(4/9-7/12) | | -6y+-14=56 | | 4/5x5/4x-3 | | 4(z+5)-24=5(z-13) | | 6x^2-13x-9=0 | | 8x+7=8x-4 | | 12x-8x-9=12-18+3x | | 2(a-15)=-2(a-3) | | 6=25m+19 | | -y=-4x+4y | | 2(a-15)=2(a+3) | | (2k+1)-(k+1)=13-(2k+1) | | 52+4X=140 | | 8t+42=58 | | 2(a-15)=-2(a+3) | | (-2)(5y^2+3y-9)= | | 6[2-(5+2x)]-2x=-20+2(1-7x) | | x+0.25x=140 | | -4(x+3)-x-7=-5(x+5)+6 | | 6k+17=37 | | 3x+7(x-10)=3(x-14) | | -4+5x-4=-4x-8-10x | | 2x-3x=5-9x+14-20 | | 18=5h+12 | | 3x=-112-5x | | 5+7t=4(t-9) | | 2x^2+27=-9 |